Identification of a 4-fluorobenzyl l-valinate amide benzoxaborole (AN11736) as a potential development candidate for the treatment of Animal African Trypanosomiasis (AAT). Issue 1 (1st January 2018) - Akama, Tsutomu; Zhang, Yong-Kang; Freund, Yvonne R.; Berry, Pamela; Lee, Joanne; Easom, Eric E.; Jacobs, Robert T.; Plattner, Jacob J.; Witty, Michael J.; Peter, Rosemary; Rowan, Tim G.; Gillingwater, Kirsten; et al.
Graphical abstract: Abstract: Novel l -valinate amide benzoxaboroles and analogues were designed and synthesized for a structure-activity-relationship (SAR) investigation to optimize the growth inhibitory activity against Trypanosoma congolense ( T. congolense ) and Trypanosoma vivax ( T. vivax ) parasites. The study identified 4-fluorobenzyl (1-hydroxy-7-methyl-1, 3-dihydrobenzo[ c ][1, 2]oxaborole-6-carbonyl)-l -valinate (5, AN11736 ), which showed IC50 values of 0.15 nM against T. congolense and 1.3 nM against T. vivax, and demonstrated 100% efficacy with a single dose of 10 mg/kg against both T. congolense and T. vivax in mouse models of infection (IP dosing) and in the target animal, cattle, dosed intramuscularly. AN11736 has been advanced to early development studies.